O Programa Institucional de Bolsas de Iniciação à Docência (PIBID) Letras - Inglês na Universidade Federal de Alagoas: a que interesses serve? - Cruz, Daniel Adelino Costa Oliveira da (2016)
This research was developed in the context of the Subproject Letters-English of PIBID-UFAL (Institutional Program of Iniciation to Teaching Scholarships at the Federal University of Alagoas). PIBID, a program of the federal government implemented by CAPES, an organ under the Ministry of Education and Culture, integrates the licensure courses offered by institutions of higher education and states and cities educational systems in order to improve teaching quality at basic education schools which display an IDEB (Basic Education Development Indicator) below national average. I have aimed at a comprehension of the relationship between PIBID and the work with the English language in Greater Maceió public schools, so as to realize which interests PIBID serves. In order to do that, I worked under the principles of XXI century Applied Linguistics (MOITA LOPES, 1996 and 2006; RAJAGOPALAN, 2003b, 1998 and 2006; PENNYCOOK 2001 and 2006; FABRÍCIO, 2006), with a concept of Science according to Sousa Santos (2010). I have established three specific objectives. To reach them, I collected, studied and analised the legislation the created and rules PIBID. I also organised meetings with supervisor teachers to collect data based on the typical procedures of narrative and life history in an autobiographical perspective (BRUNER, 2014; MERTOVA E WEBSTER, 2007; MINAYO, 1998). The analysis was carried out considering language as a social activity from a discoursive perspective (BAKHTIN, 2002), identity in post-modernity (HALL, 1992, 1997, 2011 e BHABHA, 1994), and power (FOUCAULT, 1979). My first specific objective was to know the legal contex which rules the subproject PIBID-UFAL Letters-English in order to understand which representations the law has of the professional identity of the supervisor teacher. The analysis showed me that the legal documents have two representations for this teacher: on one side, s/he is someone who has a contribution to offer, and, on the other side, s/he is someone who lacks knowledge to work efficiently and effectively. My second specific objective was to know the representations that the supervisor teachers of PIBID-UFAL Letters-English have of themselves regarding their professional identity as English teachers in the course of their pre-service educational process. The analysis showed me that they represent their professional identity as connected to the perspective of the teachers they were working to become, positioned in both public and private places. My interpretaton also showed me a representation that I called teacher-student due the the focus on their education from the perspective of the student they once were. My third and last specific objective was to know the representations this teacher has of the teaching activity in the context of the English language regarding citizenship and labour, official objectives of education as per the Brazilian Constitution in force. The narratives that I analyzed suggested two themes: the textbook and the school structure, both seen as the basis for the teaching activity. The teacher represents the quality of the activities that s/he creates as inferior to those on the textbook, which is taken as a panacea. S/he represents public schools as an undignified place, as it is unhealthy, underequipped and unsafe. I, then, came to the conclusion that, firstly, PIBID stands among actions that talk in favour of Brazilian society, but, actually, mask the real social problems sources. Secondly, low IDEB is not necessarily a result of bad teacher pre-service education. I believe that the focus on the education quality of teachers as if it were the problem of the low IDEB, as in the case of PIBID, may, actually, mean a way of making people look away from the real causes of the problem: the abandonment to which public education has been left. I hope this reflection will serve the public interests and help strengthen contemporary critical Applied Linguistics, looking to some social change that will make life better for everyone.